Maintenance chemotherapy to reduce the risk of a metachronous Wilms tumor in children with bilateral nephroblastomatosis. Issue 1 (18th October 2018) - Ortiz, Michael V.; Fernandez‐Ledon, Shannon; Ramaswamy, Kavitha; Forlenza, Christopher J.; Shukla, Neerav N.; Kobos, Rachel; Heaton, Todd E.; LaQuaglia, Michael P.; Steinherz, Peter G.
Abstract: From 2009 to 2018, 10 consecutive patients with Wilms tumors and bilateral nephroblastomatosis, who had completed standard therapy, were provided a maintenance chemotherapy regimen consisting of vincristine and dactinomycin every 3 months for 12 months in order to prevent an early metachronous Wilms tumor. One patient (10%) with Beckwith‐Wiedemann syndrome developed a new tumor, without anaplasia. There were no significant toxicities reported during maintenance. All patients are currently alive with no evidence of disease. Further investigations are recommended to determine the utility of this approach.